Паремія як засіб характеристики іспаномовної особистості (на матеріалі концепту “труд”) - Пожидаєва, О. А.; Poshidaeva, E. A. (Східноєвропейський національний університет ім. Лесі Українки, 2011)
Проаналізовано комплекс суджень про труд в іспанських прислів’ях та приказках і виявлено місце й характеристики цього поняття у свідомості іспаномовної особистості. This article attempts to analyze the complex judgments about the labor in Spanish proverbs and sayings and on the basis of this analysis to identify the place and characteristics of this concept in the minds of the Spanish language personality.
Proverbs as a Means of Personal Characteristics of the Spanish Language (on the Material Concept of “Labor”)
Keywords: концепт; паремія; іспаномовна особистість; логема; принцип антропоцентричності; concept; proverbs; Spanish language personality; logema; principle of anthropocentrism